EFFECT OF X-RAYS ON LIVER METABOLISM - Bagirov, I.M. (World of Medicine and Biology, 2023)
The experiment was carried out on 20 heads of white rats divided into 3 groups of 5 heads each. The 1st group included intact rats. Experimental animals of the 2nd group were irradiated with X rays. In white rats belonging to group 3, liver enzymes were detected in the blood 10 days after the cessation of X ray irradiation. Experimental animals were irradiated with X rays using the RUM 17 apparatus. The results of our studies showed that the concentrations of liver enzymes in the blood of white rats exposed to X ray irradiation were elevated and differed from the norm. Thus, the concentration of aspartate aminotransferase in the blood was 27 % compared to the intact state (P